2018
DOI: 10.1001/jamanetworkopen.2018.1924
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Joint Replacement Complications in Swedish Patients With a Family History of Venous Thromboembolism

Abstract: Key Points Question Is a family history of venous thromboembolism associated with postoperative venous thromboembolism and major bleeding in patients with primary hip or knee replacement surgical procedures? Findings In this cohort study of 69 505 Swedish patients, a family history of venous thromboembolism was associated with statistically significant increased venous thromboembolism risk and reduced bleeding risk after hip and knee replacement surgical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The Swedish national registers used for data extraction were: Swedish Multigeneration Register, containing data on familial relationships and index persons born in 1932 or later; National Patient Register, giving all hospital discharge diagnoses from 1964 to 2015, with nationwide coverage from 1987 and hospital outpatient diagnoses from 2001 to 2015; Total Population Register, containing data on date of death, marital status, education, and migration with high degree of coverage; and the Swedish Cause of Death Register . [13][14][15][16][17][18] The databases were linked, as previously described, [19][20][21] through the personal identity number, which is seldom incorrect. 18 Up to January 2008, an estimated 75 638 (0.56%) individuals had changed their personal identity number compared with the estimated 13 500 000 personal identity numbers in Sweden from 1969 to 31 December 2007.…”
Section: General Description Of Swedish Registersmentioning
confidence: 99%
“…The Swedish national registers used for data extraction were: Swedish Multigeneration Register, containing data on familial relationships and index persons born in 1932 or later; National Patient Register, giving all hospital discharge diagnoses from 1964 to 2015, with nationwide coverage from 1987 and hospital outpatient diagnoses from 2001 to 2015; Total Population Register, containing data on date of death, marital status, education, and migration with high degree of coverage; and the Swedish Cause of Death Register . [13][14][15][16][17][18] The databases were linked, as previously described, [19][20][21] through the personal identity number, which is seldom incorrect. 18 Up to January 2008, an estimated 75 638 (0.56%) individuals had changed their personal identity number compared with the estimated 13 500 000 personal identity numbers in Sweden from 1969 to 31 December 2007.…”
Section: General Description Of Swedish Registersmentioning
confidence: 99%
“…For instance, a recent study has shown that family history of VTE affects the risk of both VTE and major bleeding following hip and knee replacement surgical procedures. 9 It could therefore be worthwhile to determine the value of the new GRS for prediction of both VTE and bleeding.…”
mentioning
confidence: 99%
“…Activation of extremity and pulmonary thrombogenesis, by way of thromboplastin exposure, has been hypothesized to contribute to DVT and PE rates following TJA, however intraoperative steps have been taken to mitigate this process 682,689 . Manifestation of symptomatic PE is a complex, multifactorial process, with multiple pathophysiological pathways likely coexisting in genetically susceptible patients, however propagation of an extremity thrombus does not appear to consistently contribute to the burden of arthroplasty-related PE disease 690-692 .…”
Section: - Does Lower Extremity Deep Venous Thrombosis Arising After ...mentioning
confidence: 99%